The Impact of Women Directors on Firm Performance in the UK - Wang, Yanan (2019)
Among papers on corporate governance, board diversity is a hot thesis. A great number of articles have discussed the impact of board diversity on corporate performance, including gender diversity, ethnic diversity and country diversity. Those articles have got various results and different views on the influence of this relationship. But few studies focus on the board characteristics of gender diversity. This paper aims to examine the relationship between gender diversity, educational backgrounds, board experience of female directors and firm performance, according to data from the UK. This study is carried out using data of 93 firms listed on FTSE 100 from 2012 to 2017. The resources used in this paper is gained from the FAME database and annual reports of those firms. To analyse the data, two regression analyses are used, one with the dependent variable being Tobin’s Q and the other return on assets. The results in this paper show that the percentage of women directors have positive effects on firm performance, while there is no significant relationship between the educational backgrounds of women directors and firm performance. The statistics of board experience of female directors show different as it has no significant impacts on Tobin’s Q but it has negative effects on return on assets. Findings of this paper are consistent with most of board diversity researches.